Workforce size adjustment as a strategic response to exchange rate shocks: A strategy tripod application to Chinese firms - Xinming He; Marian Rizov; Xufei Zhang (Journal of Business Research, 2021)
How firms use workforce size adjustment as a strategic response to external shocks such as exchange-rate fluctuations is an important but not yet fully understood topic. To address the void in the literature, we apply the strategy tripod theoretical framework, which sees the external shocks as an industrial impact, the budget constraints as an institutional force, and the firm leverage as an organisational capability to examine the firms' strategic response in terms of workforce size adjustment in the Chinese economy context. Based on longitudinal data of Chinese manufacturing firms, our analysis finds that facing exchange rate shocks, firms with hard budget constraint are more responsive in adjusting their workforce than firms with soft budget constraint. Furthermore, highly levered firms, with hard budget constraint, will adjust their workforce more aggressively than firms with less debt in their financial structure.
Keywords: 330; HR strategy; workforce adjustment; exchange rate shocks; soft budget constraint; Chinese firms